2021
DOI: 10.1016/j.ajp.2021.102552
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of perinatal depression among women in rural Bihar: A community-based cross-sectional study

Abstract: Highlights Estimated prevalence of perinatal depression in rural Bihar, India was 23.9%. Perinatal depression is associated with mother’s physical illness and previous abortions. Poor financial status and ill-treatment by in-laws predicted perinatal depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…This has been reported by many other studies as well. A community-based cross-sectional study reported an eightfold increase in perinatal depression in mothers having physical illnesses [ 19 ]. Mothers with chronic medical ailments were reported two times more likely to develop antenatal depression [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been reported by many other studies as well. A community-based cross-sectional study reported an eightfold increase in perinatal depression in mothers having physical illnesses [ 19 ]. Mothers with chronic medical ailments were reported two times more likely to develop antenatal depression [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antenatal depression is highly associated with several sociodemographic and obstetric variables. Unplanned pregnancy; strained relationships with in-laws; physical illness [ 17 ]; history of abortions; preference for male gender [ 18 , 19 ]; alcoholism in a spouse; low education status of women [ 20 ]; multiple births; younger maternal age [ 10 ]; unplanned pregnancy family discord [ 12 ]; late pregnancy and lower or middle socioeconomic status [ 21 ]; poor/satisfactory relationship with spouse, siblings, or in-laws [ 22 ]; domestic violence; worry over the pregnancy; and history of traumatic experiences [ 23 ] were all significant predictors of depression in pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 17 18 19 ] There is scarcity of evidence from community-based study on burden of CMDs among pregnant women in India. 20 Hence, we conducted present study with the objective to assess the burden of CMDs among pregnant women in rural Haryana, North India.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggests that the rates of perinatal depression, anxiety and suicidality are higher in LMICs, as compared to countries in the West (9)(10)(11). Possible explanations for these high rates are greater stigma attached to mental health care and a lack of awareness about perinatal mental health among practitioners and mothers, which subsequently impacts prevention and treatment of mental health concerns (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, poor relations with in-laws and partners can have the opposite effect and induce omnipresent stress ( 10 , 40 ). For instance, in a cross-sectional study in Bihar, an Indian state, ill-treatment by in-laws was a predictor of antenatal depression ( 9 ). On the other hand, living in a nuclear family setting as compared to a more traditional extended household can also be a risk factor for poor antenatal mental health in urban India ( 10 ).…”
Section: Introductionmentioning
confidence: 99%